2015
DOI: 10.1016/j.jtcvs.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamic study of hemodynamic effects on aortic root blood flow of systematically varied left ventricular assist device graft anastomosis design

Abstract: Carefully chosen anastomosis geometry is likely to be able to generate a close-to-normal hemodynamic environment in the aortic root. Greater knowledge of aortic valve remodeling may make possible the creation of favorable flow patterns in the aortic root, through optimization of surgical design to reduce or delay the occurrence of aortic valve insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…The Journal of Thoracic and Cardiovascular Surgery c Volume 154, Number 3 valve leaflet thinning and, consequently, aortic valve insufficiency and its progression, 2 although computational fluid dynamics to visualize blood flow in the aortic root has not been established because of its complex anatomy, such as the origin of the coronary arteries. 3,4 We clearly visualized the blood flow in the aortic root in patients under LVAD support by conducting an echocardiographic study with vector flow mapping analysis (DAS-RS1).…”
Section: See Editorial Commentary Page 879mentioning
confidence: 99%
“…The Journal of Thoracic and Cardiovascular Surgery c Volume 154, Number 3 valve leaflet thinning and, consequently, aortic valve insufficiency and its progression, 2 although computational fluid dynamics to visualize blood flow in the aortic root has not been established because of its complex anatomy, such as the origin of the coronary arteries. 3,4 We clearly visualized the blood flow in the aortic root in patients under LVAD support by conducting an echocardiographic study with vector flow mapping analysis (DAS-RS1).…”
Section: See Editorial Commentary Page 879mentioning
confidence: 99%
“…[7][8][9][10] However, previous studies using CFD have only reported blood flow analysis in the ascending aorta without the aortic root because of the complex anatomy of the aortic root and its components such as the aortic valve, coronary arteries, and Valsalva sinus. [11][12][13][14][15] To evaluate the three-dimensional blood flow in the aortic root, three-dimensional patient-specific geometries with accurate anatomy of the aortic root were reproduced using electrocardiogram-gated 320-slice computed tomographic (CT) images. 16 We hypothesized that the blood flow pattern in the ascending aorta in patients with LVAD with AI is different from that in patients with LVAD without AI, and that the angle and position of anastomosis of the outflow graft with the ascending aorta affect the retrograde blood flow pattern in the aortic root.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dyssynchronous HF, such high-fidelity coupled models of heart function could be employed in a large variety of other cardiac problems; these include the prediction of left ventricle thrombus formation in infarcted ventricles (Son et al, 2012 ), study of systolic anterior motion (SAM) in patients with acute hypertrophic cardiomyopathy (Jiang et al, 1987 ), optimization of left ventricular-assist device (Long et al, 2014 ; Callington et al, 2015 ) implantation in patients with compromised ventricles, regurgitation in natural and prosthetic mitral valves, assessment of the effect of atrial fibrillations on cardiac performance (Koizumi et al, 2015 ), and surgical planning for procedures, such as leaflet plication (McIntosh et al, 1992 ; Padala et al, 2009 ) and hypertrophic resection (Maron, 2002 ). Such models could also be used for complex surgical therapies, such as cardiomyoplasty (El Oakley and Jarvis, 1994 ), where skeletal muscle is wrapped around a failing ventricle and activated using a pacemaker to provide cardiac assist.…”
Section: Introductionmentioning
confidence: 99%